Упростите выражение a) 5 -2(x -1) - (- 6 -x)
б) 3 ( 6,5 -y) - (-4 -2y)

mardon1 mardon1    3   29.04.2021 19:47    0

Ответы
PolliKirill PolliKirill  29.04.2021 19:50

Пошаговое объяснение:

a) 5 -2(x -1) - (- 6 -x)=5-2х+2+6+х=-х+13

б) 3 ( 6,5 -y) - (-4 -2y)=19,5-3у+4+2у=-у+23,5

ПОКАЗАТЬ ОТВЕТЫ

а) 5 -2(x -1) - (- 6 -x) = 5- 2x+2+6+x=-x+13

б) 3 ( 6,5 -y) - (-4 -2y)= 19,5- 3y + 4 +2y = -y + 23,5

Пошаговое объяснение:

а) 5 -2(x -1) - (- 6 -x) = 5- 2x+2+6+x=-x+13

б) 3 ( 6,5 -y) - (-4 -2y)= 19,5- 3y + 4 +2y = -y + 23,5

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика